2008
DOI: 10.1007/s10549-008-0194-z
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/BRCA2 mutation status and clinical-pathologic features of 108 male breast cancer cases from Tuscany: a population-based study in central Italy

Abstract: To investigate the genetic and phenotypic characteristics of MBC in a large and well-characterized population-based series of 108 MBCs from Tuscany (Central Italy) and to evaluate associations between BRCA1/BRCA2 mutation status and clinical-pathological features including breast/ovarian cancer first-degree family history, tumor histology and grade, proliferative activity, estrogen/progesterone receptors (ER/PR) and epidermal growth factor receptor 2 (HER2) expression. Results BRCA1/BRCA2 mutations were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 30 publications
3
49
0
1
Order By: Relevance
“…The association between BRCA1 mutations and MBC is not as strong as that seen for BRCA2 mutations. The lifetime risk for breast cancer in a male BRCA1 mutation carrier is just over 1%, and it is estimated that a BRCA1 mutation is present in up to 4% of MBC cases (13,25,26).…”
Section: Risk Factors For Mbcmentioning
confidence: 99%
“…The association between BRCA1 mutations and MBC is not as strong as that seen for BRCA2 mutations. The lifetime risk for breast cancer in a male BRCA1 mutation carrier is just over 1%, and it is estimated that a BRCA1 mutation is present in up to 4% of MBC cases (13,25,26).…”
Section: Risk Factors For Mbcmentioning
confidence: 99%
“…In this context, it is noteworthy that we have recently described the phenotypic characteristics of BRCA1/2-related MBCs and shown that a specific phenotype that included HER2 over-expression was associated with BRCA2-related MBCs. 16 In conclusion, the BRCAPRO 5.0 model, together with an experienced clinical evaluation, is a useful tool in selecting cases of male breast cancer for mutation analysis in the presence of MBC cases with a negative FH. In this context, the BRCAPRO 5.0 model performs better in taking account of personal history of cancer and selected tumour characteristics.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, 38% (39/102) of the patients reported a first-and/or second-degree breast-ovarian cancer FH, eight cases (8/102, 7.8%) carried a BRCA2 mutation and two cases (2/102, 2.0%) carried the same founder BRCA1 mutation. 16,18 Six of the 10 mutation carriers had a positive FH. Thus, mutation carriers account for 15.4% (6/39) of our male probands with a positive FH and for 6.4% (4/63) of those without a positive FH.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations